Study guides

☆☆

Q: What is the first derivative of 3x- 4sq root 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

let x = first number; y = second number y = 2x+7 square root of 30 = average (mean) of the two mean = sum of x+y divided by 2 (2x+7) + x = 3x+7 mean = (3x+7)/2 = sq rt 30 3x+7 = 2 x sq rt 30 3x = 2 x sqrt(30) -7 x = (2sqrt30 -7) /3 = 1.32 y = 2x+7 = 9.64

5x + 8 = 3x - 6 I always subtract the smaller x term first. In this case, it's 3x. Subtract 3x from both sides. 2x + 8 = -6 That should be a good start. ;)

There is no formula to algebra. If there were a formula, then it would have to be to do the reverse of the order of operations. For example, (3x)3 over 2=9 to figure this out, work backwards (3x)3 over 2 divided by 2=9/2 (3x)3=4.5 the square root of (3x)3=sqrt 4.5 3x=sqrt 4.5 3x/3=(sqrt 4.5)/3 x=(sqrt 4.5)/3 Technically, there is no formula, but seriously, the formula is to work backwards. Now, the problem has been turned from algebra to problem solving.

-3x + 2y = 12-3x + 3x + 2y = 3x + 122y = 3x + 122y/2 = 3x/2 + 12/2y = (3/2)x + 6

3x plus 2y can be expressed mathematically as (3x + 2y).

Related questions

4

If y = 3x +- 1, the derivative with respect to x is y' = 3.

The derivative of y = sin(3x + 5) is 3cos(3x + 5) but only if x is measured in radians.

3e3x

3sec2(3x)

In this case, you'll need to apply the chain rule, first taking the derivative of the tan function, and multiplying by the derivative of 3x: y = tan(3x) ∴ dy/dx = 3sec2(3x)

Take the derivative of (3x+1)1/2First use the power rule on the entire function, then multiply it by the derivative of the inside:(1/2)(3x-1)-1/2(3) = (3/2)(3x-1)-1/2which can also be written as3/(2sqrt(3x-1))(sqrt stands for square root)

the derivative of 3x is 3 the derivative of x cubed is 3 times x squared

4

9x2

√(24x)4/√(3x) = [242x2√(3x)]/3x = 8(24)x√(3x) = 192x√(3x)

f'(x)=-3the derivative of e is zero because its a constant. Derivative of -3x is -3. Bring the exponent of x down in front of the -3 and subtract the original exponent by 1. Ex. -3(1...which is the first exponent of the x)x^0(n-1 or 1-1=0)all this is -3(1)x^0x^0 is 1 so the derivative of -3x is -3

People also asked